Posttraumatic Stress Disorder: An Immunological Disorder? - Wang, Zhewu; Caughron, Blaine; Young, M. Rita I. (Frontiers in Psychiatry, 2017)
Patients with post-traumatic stress disorder (PTSD) exhibit an increased state of inflammation. A variety of animal models for PTSD have shown some of the same immune imbalances as have been shown in human subjects with PTSD and some of these studies are discussed in this review. However, animal studies can only indirectly implicate immune involvement in PTSD in humans. This review of mainly studies with human subjects focusses on dissecting the immunological role in the pathogenesis of PTSD following initial trauma exposure. It addresses both the inflammatory state associated with PTSD and the immune imbalance between stimulatory and inhibitory immune mediators, as well as variables that can lead to discrepancies between analyses. The concept of immunological treatment approaches is proposed for PTSD, as new treatments are needed for this devastating disorder that is affecting unprecedented numbers of Veterans from the long-standing wars in the Middle East and which affects civilians following severe trauma.